Nutrient-Induced Modifications of Wood Anatomical Traits of Alchornea lojaensis (Euphorbiaceae) - Spannl, Susanne; Homeier, Jürgen; Bräuning, Achim (Frontiers in Earth Science, 2016)
Regarding woody plant responses on higher atmospheric inputs of the macronutrients nitrogen (N) and phosphorous (P) on tropical forests in the future, an adaptive modification of wood anatomical traits on the cellular level of woody plants is expected. As part of an interdisciplinary nutrient manipulation experiment (NUMEX) carried out in Southern Ecuador, we present here the first descriptive and quantitative wood anatomical analysis of the tropical evergreen tree species Alchornea lojaensis (Euphorbiaceae). We sampled branch wood of nine individual trees belonging to treatments with N fertilization, N+P fertilization, and a control group, respectively. Quantitative evaluations of eleven different vessel parameters were conducted. The results showed that this endemic tree species will be able to adapt well to the future effects of climate change and higher nutrient deposition. This was firstly implied by an increase in vessel diameter and consequently a higher theo. area-specific hydraulic conductivity with higher nutrient availability. Secondly, the percentage of small vessels (0-20µm diameter) strongly increased with fertilization. Thirdly, the vessel arrangement (solitary vessels vs. multiple vessel groupings) changed towards a lower percentage of solitary vessel fraction (VS), and concurrently towards a higher total vessel grouping index (VG) and a higher mean group size of non-solitary vessels (VM) after N and N+P addition. We conclude that higher nutrient availability of N and N+P triggered higher foliage amount and water demand, leading to higher cavitation risk in larger vessels. This is counteracted by a stronger grouping of vessels with smaller risk of cavitation to ensure water supply during drier periods that are expected to occur in higher frequency in the near future.